HUBUNGAN PERAN GURU DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR ELEKTRONIKA DI SMK NEGERI 4 MEDAN - Mariani Pakpahan; Zainuddin Zainuddin; Rasmulia Sembiring (JURNAL PROINTEGRITA, 2019)
This study aims to determine the relationship between: (1) the role of the teacher with the learning achievement of the implementation of electronic circuits, (2) the motivation to learn with the achievement of learning the application of electronic circuits (3) the role of the teacher and learning motivation towards the learning achievement of the implementation of electronic circuits from class XI students of SMK Negeri 4 Medan 2017/2018 Academic Year. The population used in this study were students of class XI Audio Video Engineering Program 2017/2018 Academic Year which amounted to 76 respondents and all of them were used as research samples.Data was collected by questionnaire techniques for teacher role variables and student learning motivation variables and value documents for the subjects of the application of electronic circuits. Data were analyzed using product moment correlation and multiple correlation analysis.From the results of the analysis it can be concluded: (1) there is a significant and positive relationship between the role of the teacher and student achievement in the subject of the application of electronic circuits (r 0.465 = medium), (2) there is a significant and positive relationship between student motivation and achievement learning on the subject of the application of electronic circuits (r 0.337 = low), (3) there is a significant and positive relationship between the role of the teacher and the learning motivation of students with learning achievement in the subject of the application of electronic circuits (r 0.515 = medium).